Hubungan Antara Pengungkapan-Diri dan Kepuasan Pernikahan dengan Dimediasi oleh Intimasi - Arif Romdhon; Hepi Wahyuningsih (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
The present study was aimed to examine the relationship between self-disclosure and marital satisfaction, and whether the relation between self-disclosure and marital satisfaction meditated by intimacy. The participants of study involved 110 individual married peoples in Cilegon, Banten. As predicted, the result showed that selfdisclosure was positively related to marital satisfaction. Furthermore, the result also showed that intimacy was mediator the relationship between self-disclosure and marital satisfaction. Implications and directions for future research were discussed.Keywords: Self-disclosure, intimacy, Marital Satisfaction